The Role of Regional Technical Implementation Units in Advancing Inclusive Education for Persons with Disabilities in Indonesia - Aspan, Hamida; Hermanto, Hermanto (Papanda Publisher, 2025)
Despite comprehensive regulatory frameworks supporting inclusive education in Indonesia, significant gaps persist between policy formulation and practical implementation for persons with disabilities. This study examines the role of Regional Technical Implementation Units (UPTD) in bridging these gaps through comprehensive service delivery mechanisms. This qualitative descriptive study employed a phenomenological approach to investigate UPTD Disability Services and Inclusive Education's role in enhancing inclusive education for persons with disabilities in Samarinda City. Data were collected through semi-structured interviews with key informants including the Head of UPTD PLDPI, school principals, and teachers, complemented by direct observations and documentation analysis. Data validity was ensured through triangulation techniques, while analysis followed Miles, Huberman, and Saldana's interactive model. UPTD PLDPI performs four primary roles: developing inclusive education policies, providing facilities and support services, enhancing teacher competencies, and promoting community awareness. The institution has facilitated inclusive education implementation in 178 schools serving 840 students with disabilities. However, significant challenges persist including insufficient community awareness, limited human resources and budget constraints, inadequate curriculum development, and insufficient infrastructure. The gap between 1,730 total persons with disabilities and 840 enrolled students indicates substantial access limitations. The findings reveal both progress and persistent barriers in inclusive education implementation. While UPTD PLDPI demonstrates institutional adaptability and policy responsiveness, systemic challenges require coordinated multi-stakeholder approaches. The research contributes to understanding how regional technical units function as intermediary mechanisms between policy formulation and practical implementation, emphasizing the necessity for enhanced coordination, comprehensive teacher preparation, systematic community engagement, and sustained resource allocation for effective inclusive education delivery.